Pengaruh Harga dan Kualitas Pelayanan terhadap Keputusan Nasabah Menggunakan Produk Pembiayaan Pensiun pada Bank Syariah Mandiri Kantor Cabang Padang Ulak Karang - Febsri Susanti; Amalia Martha (JURNAL PUNDI, 2020)
The purpose of this study was to study and analyze the price and quality of services to spending decisions using financial products at Bank Syariah Mandiri, Padang Ulak Karang Branch Office.The research method used is descriptive quantitative. Based on the regression analysis, multiple linear price variables and service quality towards spending decisions using award financing products at PT. Bank Syariah Mandiri Branch Office of Padang Ulak Karang obtained Y = 16,284 + 0.472X1-0192 X2 + 0.229 X3-0.709 X4-0.161 X5 + 0.683 X6 + e.The results of this study only determine the price and empathy that is positive and significant to real decisions, reliability, responsiveness, guarantees are negatively related and not significant to decision making.Keywords: price, service quality and expenditure decisions.